Baritan Malam Satu Suro: Islamic Traditions in Winong Village Ngampel District Kendal Regency - Muhamad Solihin; Khofifatus Sholihah; Brynita Dayu Adesti (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Baritan Malam Satu Suro is one of the traditions rich in spiritual and cultural values ​​in Winong Village, Ngampel District, Kendal Regency. This study examines the meaning and implementation of the Baritan tradition in the context of Islamic religion. This study uses qualitative research with participatory observation methods and in-depth interviews with community leaders and event participants. The results of the study indicate that Baritan Malam Satu Suro is not only a form of gratitude to Allah, but also an effort to strengthen the ties of friendship between villagers. This tradition involves rituals such as joint prayers, reading of holy verses, and traditional processions reflecting local wisdom. In addition, this event also functions as a means of educating Islamic values ​​to the younger generation. These findings are expected to enrich the understanding of tradition's role in strengthening the Islamic community's identity in rural areas.